3D CAD/reverse engineering technique for assessment of Thai morphology: Proximal femur and acetabulum - Nattapon Chantarapanich (2018)
© 2017 The Japanese Orthopaedic Association Purpose To assess morphological parameters of proximal femur and acetabulum in Thai population with three-dimensional measurement technique, and to analysis of collateral side symmetric, gender difference, and correlation between morphometric parameters. Methods Investigation was performed in 240 femurs. All three-dimensional femur models were acquitted from 64-slice spiral CT scanner. Morphometric parameters under consideration included acetabular diameter, femoral head diameter, shaft isthmus location, intramedullary canal diameter, diaphyseal diameter, femoral head height, femoral neck isthmus, femoral neck length, neck shaft angle, bow angle, and anteversion angle. All parameters were measured based on functions and least-square regression function in CAD software. Obtained measured data were then used for analysis of collateral side symmetric, gender difference, correlation between morphometric parameters, and compared with other populations. Results Female had a smaller dimension compared with male in most of the parameters. No significant difference was observed between left and right femurs. High correlation pairs of morphometric parameters included femoral head diameter–acetabular diameter, femoral head diameter–neck isthmus diameter, femoral head diameter–diaphyseal diameter at shaft isthmus level, acetabular diameter–neck isthmus diameter, neck isthmus diameter–diaphyseal diameter at shaft isthmus level, and acetabular diameter–diaphyseal diameter at shaft isthmus level. Some morphometric parameters of Thai are smaller than other Caucasian, and some Asian nation, i.e. femoral head diameter, femoral neck length, and femoral head height. Conclusions This study provides essential morphometric data for various orthopedic implant designs relating to proximal femur region.